Why are we tracking Reception-aged children? Teachers’ and key stakeholders’ perspectives on the reintroduction of national Reception Baseline Assessment - David Meechan; Tracy Whatmore; Zeta Williams-Brown; Simon Halfhead (Educational Futures, 2022)
This paper considers the recent development and implementation of statutory Reception Baseline Assessment (RBA) in England introduced by the Department for Education (2021). Internal baseline assessments, undertaken by early years professionals, have traditionally been an integral part of gaining informed knowledge and understanding of individual children in Reception classes. Previous iterations of baseline assessment have included observations and interactions with children in order to begin to construct an overview of their holistic development, their experience, abilities, skills, strengths, and areas for development (TES, 2015). Such types of assessment are used by early years teachers and practitioners to inform learning and teaching during children’s first year of primary school (Brodie, 2013). In 2021, the RBA statutory guidance (DfE) established a formal assessment process for assessing all Reception-aged children within six weeks of starting primary school.